Taxonomy and morphology of species of the genus Squalus Linnaeus, 1758 from the Southwestern Atlantic Ocean (Chondrichthyes: Squaliformes: Squalidae) - Viana, Sarah T. De F.; Carvalho, Marcelo R. De; Gomes, Ulisses L. (Zootaxa, 2016)
Squalus is a genus of reportedly cosmopolitan shark species that have a high taxonomic complexity due to difficulties in their morphological differentiation; many of its species need revision. Currently, there are 26 valid species of Squalus, which have been divided into three species-groups according to overall morphological similarity, the S. acanthias, S. megalops, and S. mitsukurii groups. Loss of type specimens, propagation of erroneous identifications in the literature, and difficulties in obtaining representative series for comparison are secondary challenges that have impeded a global taxonomic revision of the genus. This problem applies clearly to species from the Southwestern Atlantic Ocean, including species that occur off Brazil. Following a current global tendency, a regional taxonomic revision of Squalus was conducted in order to investigate which species are valid in the Southwestern Atlantic Ocean and provide diagnostic morphological characters that can be efficiently used for identifying species. Comparative detailed analysis of external (e.g. morphometrics, dentition, and color pattern) and skeletal morphology (primarily meristic data, neurocrania and claspers) of specimens of Squalus from the region revealed four new species that are herein described (S. albicaudus sp. nov., S. bahiensis sp. nov., S. lobularis sp. nov., and S. quasimodo sp. nov.), as well as S. acanthias, which is redescribed from the region based on new material. Comparisons are offered based on examinations of congeneric species; this work is part of a global systematic revision of Squalus.